Synthesis of chiral boranes via asymmetric insertion of carbenes into B–H bonds catalyzed by the rhodium( i ) diene complex - Ankudinov, Nikita M.; Komarova, Alina A.; Podyacheva, Evgeniya S.; Chusov, Denis A.; Danshina, Anastasia A.; Perekalin, Dmitry S. (Chemical communications (Cambridge, England), 2024)
Molecules with chiral boron atoms have been scarcely studied due to limited synthetic access. Herein, we report a new method for their synthesis via asymmetric insertion of arydiazoacetates into the B–H bonds of prochiral carbene–boranes NHC–BH 2 R. The reaction is catalyzed by the rhodium( i ) complex with the chiral diene ligand t Bu 2 -TFB, which can be conveniently prepared by diastereoselective coordination of the racemic diene with ( S -Salox)Rh(CO) 2 . The target boranes were typically obtained in 75–90% yields with 90–95% ee.